Smart-Cerdik: Model Pemberdayaan Lansia Berbasis Digital dan Family Support Dalam Pencegahan Hipertensi dan Risiko Stroke di Komunitas - Tri Wahyuni Ismoyowati; Wylianty Rahardjo; Eddy Suharso; Aryaprana Nando; Hari Iskandar Kang (Jurnal Medika: Medika, 2026)
Biology, as a branch of natural science, requires not only mastery of theoretical concepts but also practical application to enhance students' understanding of biological phenomena. This community service activity aims to implement biology practices through the creation of an insectarium as a learning medium for high school students at the Raudhatul Ulum Islamic Boarding School in Ogan Ilir Regency. The implementation method used a socialization approach, material presentation, demonstrations, hands-on practice, and interactive discussions. This activity was also supported by the use of computer-based media and simple laboratory equipment. Student understanding was evaluated using pre- and post-socialization questionnaires with five main indicators: knowledge of insect types, insectarium terms, purposes and benefits, tools and materials, and the stages of insectarium construction. The results of the activity showed an increase in student understanding after the socialization, characterized by an increased ability to systematically understand the concepts, functions, and processes of insectarium construction. This activity also improved students' practical skills, accuracy, and scientific attitudes through hands-on, experiential learning. Thus, the practical application of biology through the creation of an insectarium has proven effective in improving students' understanding and skills, making it a viable alternative for practical and contextual biology learning media at the secondary school level.